A Concept Analysis: Tenacity of Post-Stroke Patients in Rehabilitation Programs - Anderson, Elisa (NUTRIX, 2024)
Stroke is a major global health issue, with rehabilitation offering significant benefits. However, adherence is often compromised. Tenacity, defined by persistence and determination, is essential for effective rehabilitation but is often overlooked and poorly evaluated in clinical settings. This analysis aims to clarify the concept of tenacity in post-stroke rehabilitation and assess its impact on outcomes. Walker and Avant's eight-step framework is used to examine tenacity, drawing data from relevant stroke rehabilitation literature. The analysis reveals that tenacity has several key attributes, including adaptability, self-motivation, determination, perseverance, resilience, and persistence. Antecedents of tenacity include factors such as the severity of the stroke, family support, and access to rehabilitation resources. High levels of tenacity lead to improved rehabilitation outcomes, such as enhanced mobility and quality of life. Tenacity is an essential component in the rehabilitation of post-stroke patients that can significantly improve rehabilitation outcomes. A better understanding of tenacity can aid healthcare professionals in designing more effective interventions to support patients in their rehabilitation programs. Further research is needed to develop valid and reliable tools for assessing tenacity and to evaluate interventions that can enhance patient tenacity.